Deactivation of electrodes and influence in speech perception in patients with cochlear implant - Santana Júnior, Carlos Alberto Conceição (2024)
Background: Despite continued advances in electrode design, processing strategies, and Cochlear Implant (CI) technology, there are situations that demand disable electrode deactivation, negatively impacting CI users speech perception. Objective: to characterize the results of speech recognition in CI users who underwent electrode deactivation due to subjective complaints or objective findings improper functioning of the electrodes. Research Design: Retrospective Review. Study sample: Forty-six users of devices from Advanced Bionics®, Med-EL® or Cochlear®, participating in the study. The inclusion criteria covered CI users who had full insertion of electrodes and needed to deactivate electrodes during follow-up, effective use of the device, absence of sensory deprivation, capacity for auditory recognition in an open environment, have all electrodes inserted intracochlearly, confirmed after post-operative imaging exams and need for deactivation during follow-up. Intervention: Assessment of speech recognition in CI users with deactivated electrodes. Data Collection and Analysis: Analysis of programming records and hearing performance data before and after electrode deactivation. Results: No significant differences were observed in the results of free-field audiometry and sentence recognition tests in silence and noise before and after deactivating the electrodes. Furthermore, no significant correlations were identified between performance, number of electrodes deactivated and time interval after deactivation. Conclusions: The results indicate that poorer encode electrodes deactivation did not influence speech recognition attributes in quiet and noisy environments, as well as free field audiometry thresholds in our study.